How to Do Everything NetObjects Fusion 11 - PLotkin David N (New York : Mc Graw Hill, 2009)
Get up and running quickly on the latest version of the complete, do-it-yourself web site design software. How to Do Everything: NetObjects Fusion 11 explains how to navigate the interface, configure the toolbars and panels, create web sites and pages, position and format text, and include graphics and audio. You'll get tips for designing and structuring your site, and adding advanced functionality, such as search capability, site mapping, forms, FAQs, Guestbooks, and security. Design, develop, publish, and manage your NetObjects Fusion 11 web site with ease using this hands-on guide.
Build a web site template and pages
David Plotkin designs computer systems, databases, and websites. He is the author of How to Do Everything with Photoshop Elements 3 and How to Do Everything with Microsoft FrontPage.
Keywords: NetObjects Fusion; Web sites --Design